Carbon storage in coastal wetlands is related to elevation and how it changes over time. (5th April 2022) - Owers, Christopher J.; Woodroffe, Colin D.; Mazumder, Debashish; Rogers, Kerrylee
Abstract: National and global scale initiatives to reduce loss and promote restoration of coastal ecosystems have leveraged the capacity of mangrove and saltmarsh to contribute to climate change mitigation through carbon sequestration. The success of these programs is predicated on reliable estimates of carbon storage and how this changes over time. Efforts to describe spatial variation in below-ground carbon storage have largely focussed on surface sediments, with few studies able to characterise carbon at greater soil depths. This study demonstrates that landscape position occupied by wetland vegetation influences both carbon storage and sources, and that understanding evolutionary infill of estuaries is crucial for characterising spatial variation in carbon storage. We focussed on coastal wetlands in southeast Australia where sea level has a long history of relative stability over the past few millennia. Under these conditions, we show that carbon storage varies across three depth zones in substrate: the active root zone (associated with distribution of contemporary vegetation), inactive root zone (associated with past environmental conditions) and subtidal zone (beyond the contemporary intertidal zone). This conceptual approach relates spatial variation in carbon storage to key processes influencing carbon addition and decomposition, and can be applied elsewhere depending on the sea-level history at the specific site. We demonstrate that models that define carbon storage in the context of variation in landscape position of vegetation in the tidal frame provide improved confidence required for blue carbon assessments. Graphical abstract: Image 1 Highlights: Wetland vegetation position in the landscape influences carbon storage. Carbon in sediments varies with depth of substrate. Spatial models conceptualising variation with depth will improve carbon storage estimates.